Well built Mycenae : the Helleno-British excavations within the citadel at Mycenae, 1959-1969 - Shelton, Kim S., (Archaeopress Publishing Ltd, 2022)
Presenting results of excavations in the 'Cult Centre' area at Mycenae, the Tsountas House Area contains two buildings and multiple access ramps. This study is essential for understanding the conception and function of Mycenaean religious space and the socio-political development of cult.